2018
DOI: 10.1002/anie.201802420
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Precise Nanocluster Assemblies Encapsulating Plasmonic Gold Nanorods

Abstract: The self-assembled structures of atomically precise, ligand-protected noble metal nanoclusters leading to encapsulation of plasmonic gold nanorods (GNRs) is presented. Unlike highly sophisticated DNA nanotechnology, this strategically simple hydrogen bonding-directed self-assembly of nanoclusters leads to octahedral nanocrystals encapsulating GNRs. Specifically, the p-mercaptobenzoic acid (pMBA)-protected atomically precise silver nanocluster, Na [Ag (pMBA) ], and pMBA-functionalized GNRs were used. High-resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 31 publications
0
62
0
Order By: Relevance
“…For example, attaching AuNCs to silver or gold spherical nanoparticles resulted in an improved photoelectric or photocatalytic performance of the nanoclusters. 7,40 In reverse, AuNCs were used to improve the photothermal 41,42 and/or optical 43,44 properties of AuNRs. Au and Ag nanoclusters were also assembled with plasmonic nanoparticles to study the alteration of their emission properties.…”
Section: Introductionmentioning
confidence: 99%
“…For example, attaching AuNCs to silver or gold spherical nanoparticles resulted in an improved photoelectric or photocatalytic performance of the nanoclusters. 7,40 In reverse, AuNCs were used to improve the photothermal 41,42 and/or optical 43,44 properties of AuNRs. Au and Ag nanoclusters were also assembled with plasmonic nanoparticles to study the alteration of their emission properties.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembly provides an alternative method to customize or enhance the materials properties and performance of metal NCs through the collective and synergistic effects of adjacent NCs in the assembly, which can be fabricated in different sizes, morphologies, symmetries, and orders. 106,108,[128][129][130][131]186 Since the self-assembly process of metal NCs is mainly governed by either the inter-cluster interactions/reactions or clusters' interactions/ reactions with the cross-linker ions/molecules, superstructures with 1D, 2D and 3D congurations have been constructed based on metal NCs by deliberately controlling such interactions/ reactions.…”
Section: Molecular Interactions/reactions In Self-assembly Of Metal Ncsmentioning
confidence: 99%
“…For example, Chakraborty et al assembled [Ag 44 ( p -MBA) 30 ] 4− around p -MBA protected Au nanorods (Au NRs) with a length of ∼30 nm and a width of ∼10 nm. 186 The preferential anchoring of [Ag 44 ( p -MBA) 30 ] 4− on the <110> facets of Au NRs via H-bonds was suggested to trigger the self-assembly of [Ag 44 ( p -MBA) 30 ] 4− , ultimately giving rise to a core-in-cage octahedral architecture of Au NR@Ag 44 NCs. In sharp contrast to Au NR directed self-assembly of [Ag 44 ( p -MBA) 30 ] 4− NCs, the self-assembly behaviour of Te nanowires (NWs) can be modulated by [Ag 44 ( p -MBA) 30 ] 4− NCs.…”
Section: Molecular Interactions/reactions In Post-synthesis Development Of Metal Ncsmentioning
confidence: 99%
“…One of the recent studies by Pradeep’s group showed that simple hydrogen bonding could also direct the self-assembly of NCs using the previously discussed ligand p-MBA. Gold nanorods were functionalized with p-MBA, and Ag 44 NCs were allowed to interact with this GNR@p-MBA, which resulted in directed self-assembly ( Figure 6 A) [ 78 ]. Ag 44 NCs form assembly through H-bonding with carboxylic acid dimerization of the capped surface ligands.…”
Section: Nanoscale Forces On Assemblymentioning
confidence: 99%